Agency Cost, Financial Performance, And Women in Board of Commissioners - Wijaya, Hendra (Jurnal Keuangan dan Perbankan, 2021)
This study aims to examine the influence of agency costs on financial performance and women on the board of commissioners on the influence of agency costs on financial performance. The sample in this study is a non-financial company listed on the Indonesian stock exchange in 2014-2018. Data analysis was performed using panel data regression. This study indicates that agency costs negatively influence financial performance, and the existence of women on the board of commissioners can reduce the negative influence of agency costs on financial performance. It is indicated that women on the board of commissioners increase the alignment of principals and management. Women in the board of commissioners increase the board's ability to monitor the agent when making the decision, and women have characteristics such as risk-averse, conservatism, and ethics.JEL: G23, G32, J16